Associated factors with voriconazole plasma concentration: a systematic review and meta-analysis - Li, Xiaoqi; Hu, Qiaozhi; Xu, Ting (Frontiers in Pharmacology, 2024)
Background: Voriconazole plasma concentration exhibits significant variability and maintaining it within the therapeutic range is the key to enhancing its efficacy. We conducted a systematic review and meta-analysis to estimate the prevalence of patients achieving the therapeutic range of plasma voriconazole concentration and identify associated factors.Methods: Eligible studies were identified through the PubMed, Embase, Cochrane Library, and Web of Science databases from their inception until 18 November 2023. We conducted a meta-analysis using a random-effects model to determine the prevalence of patients who reached the therapeutic plasma voriconazole concentration range. Factors associated with plasma voriconazole concentration were summarized from the included studies.Results: Of the 60 eligible studies, 53 reported the prevalence of patients reaching the therapeutic range, while 21 performed multiple linear regression analyses. The pooled prevalence who achieved the therapeutic range was 56% (95% CI: 50% to 63%) in studies without dose adjustment patients. The pooled prevalence of adult patients was 61% (95% CI: 56 to 65%), and the pooled prevalence of children patients was 55% (95% CI: 50 to 60%) The study identified, in the children population, several factors associated with plasma voriconazole concentration, including age (coefficient 0.03, 95% CI: 0.02 to 0.04), albumin (-0.04, 95% CI: -0.06 to -0.01), in the adult population , some factors related to voriconazole plasma concentration, including omeprazole (1.14, 95% CI: 0.06 to 1.68), pantoprazole (1.11, 95% CI: 0.17 to 2.04), methylprednisolone (-1.75, 95% CI: -2.21 to -1.30), and dexamethasone (-1.45, 95% CI: -2.07 to -0.83).Conclusions: The analysis revealed that only approximately half of the patients reached the plasma voriconazole concentration therapeutic range without dose adjustments and the pooled prevalence of adult patients reaching the therapeutic range is higher than that of children. Therapeutic drug monitoring is crucial in the administration of voriconazole, especially in the children population. Particular attention may be paid to age, albumin levels in children, and the use of omeprazole, pantoprazole, dexamethasone and methylprednisolone in adults.